OPTIMISATION OF LAND MORTGAGE MANAGEMENT IN CORPORATE FINANCING: A CIVIL LAW STUDY AND ITS IMPACT ON BUSINESS LIQUIDITY - Hadenan Towpek; Teti Anggita Safitri (Adisam Publisher, 2026)
This article analyses the optimisation of land mortgage management as a strategic instrument for corporate financing from a civil economic perspective and its impact on business liquidity. Based on a legal-normative literature review of Law No. 4 of 1996, Book III of the Civil Code, and a case study of a state-owned construction company, the research proves that the parate executie doctrine and the preference system (prior tempore potior jure) increase the recovery rate by 82% in 12 months, the current ratio by 1.5x, and asset turnover by 2.3x through refinancing and multi-ranking HT. Systemic optimisation of HT reduces WACC by 2.5%, accelerates the velocity of money by 1.3x, and has the potential to channel Rp450 trillion in real credit by 2026 to support the GDP target of 5.2%. Recommendations include digitising BPN SHT, ABS-HT securitisation, and a single BPN-bank window to eliminate overlapping authorities that cause a 24-month holding period. These findings are relevant for legal practitioners, financial managers, and policymakers for the transformation of the land-based financing ecosystem towards an inclusive and resilient economy amid global volatility in 2026.